Gonadal characterization of the Amazonian fish Serrapinnus kriegi (Characidae: Cheirodontinae) - Felicio, G. R.; Cordeiro, J. G. [UNESP]; Dutra-Costa, B. P.; Maximino, C.; Branco, G. S. [UNESP]; Quirino, P. P. [UNESP]; Siqueira-Silva, D H de (FapUNIFESP (SciELO), 2021)
The knowledge of the testicular and ovarian morphology of a particular fish species is of paramount importance. Such analyze enables the development of studies and techniques aiming the improvement of their reproduction, management, commercialization and even their conservation. This study performed the ovarian and testicular characterization of the ornamental Amazon fish Serrapinnus kriegi. A total of three males and three females had their gonads analyzed by optical microscopy. Females present ovaries filled with oocytes in asynchronous development, indicating partial spawning in the species. Moreover, the micropyle and micropilar cell formation was observed in primary growing oocytes, representing a precocious oocyte development; and the zona radiata in the final vitellogenic oocytes is thicker than other related species, evidencing the development of a better protection to the embryos in function of the waters' turbulence that characterize it spawning sites in the Amazonian streams. The male specimens' present anastomosed tubular testes with unrestricted spermatogonia spread along the entire seminiferous tubules. The present data elucidate the dynamic of spermatogenesis and oogenesis of an ornamental Amazonian species, through the description of the male and female germ cells development.